Functional hyposplenism is an important and underdiagnosed immunodeficiency condition in children. (31st July 2014) - Scheuerman, O.; Bar‐Sever, Z.; Hoffer, V.; Gilad, O.; Marcus, N.; Garty, B.Z.
Abstract Aim Few studies have focused on paediatric hyposplenism/asplenism, in which splenic phagocytic activity is diminished or absent in an anatomically present spleen. This study aimed to evaluate clinical findings, laboratory tests and prognosis of children with functional hyposplenism/asplenism. Methods The study group comprised 74 children who had liver/spleen technetium‐99m sulphur colloid scintigraphy from 2002 to 2008. Information collected included demographic features, background diseases, blood smear findings, indications for scintigraphy and outcome. Children with functional hyposplenism were followed until 2012. Results We found that 34 patients had functional hyposplenism/asplenism. The main indications for scintigraphy in the hyposplenic patients were persistent thrombocytosis and recurrent infections. Associated conditions included immunodeficiencies, autoimmune diseases, malignancies and genetic disorders. Main infections were sinopulmonary infections, bacteraemia and sepsis. The major pathogens were Streptococcus pneumoniae and Haemophilus influenza group A. There was no correlation between the presence of Howell‐Jolly bodies in blood smear with clinical disease severity or scintigraphic findings. Repeated scintigraphy showed spontaneous normalisation in 40% of patients. Conclusion Functional hyposplenism is an important and underdiagnosed immunodeficiency condition in children, associated with various clinical conditions including prolonged unexplained thrombocytosis, immune deficiency and autoimmunity. Technetium‐99m sulphur colloid scintigraphy is the method of choice for evaluating splenic function.